Optimization of the mean-variance investment portfolio of some stocks under market sentiment and the ARMAX-GARCH model - Hasbullah E.S.; Sukono; Rusyaman E.; Suyudi M.; Kalfin; Halim N.B.A. (Science and Engineering Research Support Society, 2024)
Indexed by SCOPUS/ERA